2011
DOI: 10.1073/pnas.1108482108
|View full text |Cite
|
Sign up to set email alerts
|

Antitumorigenic potential of STAT3 alternative splicing modulation

Abstract: Signal transducer and activator of transcription 3 (STAT3) plays a central role in the activation of multiple oncogenic pathways. Splicing variant STAT3β uses an alternative acceptor site within exon 23 that leads to a truncated isoform lacking the C-terminal transactivation domain. Depending on the context, STAT3β can act as a dominant-negative regulator of transcription and promote apoptosis. We show that modified antisense oligonucleotides targeted to a splicing enhancer that regulates STAT3 exon 23 alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
124
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(128 citation statements)
references
References 38 publications
2
124
2
Order By: Relevance
“…More recent studies have demonstrated that STAT3b may activate a specific set of genes and possess non-redundant functions to STAT3a. Zammarchi et al used morpholino oligomers to redirect endogenous STAT3 alternative splicing from STAT3a to STAT3b (Zammarchi et al, 2011). This study showed that inducing the STAT3b isoform in MDA-MB-435 cells caused cell death and tumor regression in the xenograft models.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…More recent studies have demonstrated that STAT3b may activate a specific set of genes and possess non-redundant functions to STAT3a. Zammarchi et al used morpholino oligomers to redirect endogenous STAT3 alternative splicing from STAT3a to STAT3b (Zammarchi et al, 2011). This study showed that inducing the STAT3b isoform in MDA-MB-435 cells caused cell death and tumor regression in the xenograft models.…”
Section: Discussionmentioning
confidence: 83%
“…The same study showed that STAT3 canonical target genes were not affected by the switch from STAT3a to STAT3b. Rather, a unique expression signature seems to be associated with the physiological a-to-b splicing shift (Zammarchi et al, 2011). In mammary gland development, it has become clear that STAT3 regulates a complex series of processes involving alveolar epithelial cell death during involution by maintaining the balance of inflammatory and anti-inflammatory signaling (Pensa et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…STAT3 is of particular interest because of its pleiotropic and uncertain functionality, with conflicting reports on whether it acts as an oncoprotein or tumor suppressor in cancer (reviewed in reference 33 ). Differences in STAT3 α and β splice variant function had been characterized previously 34,35 , and our protocol facilitated a knock-down/re-expression analysis that suggests a need for an optimal ratio of S and ΔS transcripts 19 .…”
Section: Discussionmentioning
confidence: 99%